2011
DOI: 10.2140/pjm.2011.250.257
|View full text |Cite
|
Sign up to set email alerts
|

Realizing profinite reduced special groups

Abstract: Special groups are an axiomatization of the algebraic theory of quadratic forms over fields. It is known that any finite reduced special group is the special group of some field. We show that any special group that is the projective limit of a projective system of finite reduced special groups is also the special group of some field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…. , β n ≡ G v ⊕ χ, that, together with the first isometry in (5), completes the proof of (b) and of Fact 6.…”
Section: Monomorphisms In the Category Of Special Groupssupporting
confidence: 58%
See 1 more Smart Citation
“…. , β n ≡ G v ⊕ χ, that, together with the first isometry in (5), completes the proof of (b) and of Fact 6.…”
Section: Monomorphisms In the Category Of Special Groupssupporting
confidence: 58%
“…In the forthcoming paper [5] it is shown that any profinite reduced special group is isomorphic to the special group associated to a Pythagorean field.…”
Section: Profinite Special Groupsmentioning
confidence: 99%
“…At the same time, it remains an open problem whether profinite spaces of orderings are realizable. We note here that the dual question of whether direct limits of finite spaces of orderings are realizable was partially answered already in the early 1980s in [8], and recently completely resolved in [1].…”
mentioning
confidence: 88%